The MEF2A transcription factor interactome in cardiomyocytes - Moustafa, Amira; Hashemi, Sara; Brar, Gurnoor; Grigull, Jörg; Ng, Siemon H. S.; Williams, Declan; Schmitt-Ulms, Gerold; McDermott, John C. (Cell death & disease, 2023)
Transcriptional regulators encoded by the M yocyte E nhancer F actor 2 (MEF2) gene family play a fundamental role in cardiac development, homeostasis and pathology. Previous studies indicate that MEF2A protein-protein interactions serve as a network hub in several cardiomyocyte cellular processes. Based on the idea that interactions with regulatory protein partners underly the diverse roles of MEF2A in cardiomyocyte gene expression, we undertook a systematic unbiased screen of the MEF2A protein interactome in primary cardiomyocytes using an affinity purification-based quantitative mass spectrometry approach. Bioinformatic processing of the MEF2A interactome revealed protein networks involved in the regulation of programmed cell death, inflammatory responses, actin dynamics and stress signaling in primary cardiomyocytes. Further biochemical and functional confirmation of specific protein-protein interactions documented a dynamic interaction between MEF2A and STAT3 proteins. Integration of transcriptome level data from MEF2A and STAT3-depleted cardiomyocytes reveals that the balance between MEF2A and STAT3 activity exerts a level of executive control over the inflammatory response and cardiomyocyte cell survival and experimentally ameliorates Phenylephrine induced cardiomyocyte hypertrophy. Lastly, we identified several MEF2A/STAT3 co-regulated genes, including the MMP9 gene. Herein, we document the cardiomyocyte MEF2A interactome, which furthers our understanding of protein networks involved in the hierarchical control of normal and pathophysiological cardiomyocyte gene expression in the mammalian heart.